1)a)[tex] 2x^{2} =1-(-1)^{2013}
[/tex]
[tex]2 x^{2} =2[/tex]
[tex] \frac{ 2x^{2} }{2} = \frac{2}{2} [/tex]
x=±√1x=1 or x=−1
2)a)6x(5x+3)=18x
[tex] 30x^{2} +18x=18x [/tex]
[tex]30 x^{2} +18x-18x=18x-18x [/tex]
[tex] 30x^{2} =0 [/tex]
[tex] \frac{30 x^{2} }{30} = \frac{0}{30} [/tex]
[tex] x^{2} =0[/tex]
x=±√0x=0
b)(x+2)²+(x−2)²=80
2x²+8=80
2x²+8−8=80−8
2x²=72
[tex] \frac{ 2x^{2} }{2} = \frac{72}{2} [/tex]
x²=36
x=±√36x=6 or x=−6
c)3x²−4=4−3x²
3x²−4=−3x²+4
3x²−4+3x²=−3x²+4+3x²
6x²−4=46x²−4+4=4+46x²=8
[tex] \frac{ 6x^{2} }{6} = \frac{8}{6} [/tex]
[tex] x^{2} = \frac{4}{3} [/tex]
x=±[tex] \sqrt{ \frac{4}{3} } [/tex]
x=1.154701,−1.154701